Komitmen Organisasional, Kepuasan Kerja, Kepemimpinan Transformasional dan Pengaruhnya terhadap Organizational Citizenship Behavior - Widiyanti Nur Chabib; Tri Harsini Wahyuningsih (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2022)
The purpose of this study was to analyze organizational commitment, job satisfaction, transformational leadership, and its effect on organizational citizenship behavior (OCB) at the regional water company (PDAM). This company is a source of local revenue that is engaged in providing clean water for the community. Data were taken using a questionnaire from a sample of 130 permanent employees who were determined by purposive sampling using the Slovin method. Data analysis used t test, multiple linear regression, and F test. Partially, organizational commitment had no effect on OCB, while job satisfaction had a positive effect (0.234) and significant (0.018) on OCB. Transformational leadership has a positive (0.497) and significant (0.000) effect on OCB. Simultaneously organizational commitment, job satisfaction, and transformational leadership affect OCB.